RESOLUTION OF SHARIA ECONOMIC DISPUTES BY CERTIFIED JUDGES BASED ON SUPREME COURT REGULATION NUMBER 5 OF 2016 CONCERNING CERTIFICATION OF SHARIA ECONOMIC JUDGES AT THE SUNGGUMINASA CLASS 1B RELIGIOUS COURT - Muh. Syahril A; Muhammadiyah Amin; Sippah Chotban (Iqtishaduna: Jurnal Ilmiah Mahasiswa Hukum Ekonomi Syariah, 2025)
Abstract The subject matter of this research is how the settlement of sharia economic disputes by certified judges based on PERMA Number 5 of 2016 concerning Certification of Sharia Economic Judges at the Sungguminasa Class 1B Religious Court. The sub-problems are: 1) How is the process of resolving sharia economic disputes at the Sungguminasa Class 1B Religious Court? 2) How is the competence of the judge of the Sungguminasa Class 1B Religious Court in resolving sharia economic disputes based on PERMA Number 5 of 2016 concerning Certification of Sharia Economic Judges? This type of research is descriptive qualitative field research with a juridical-empirical approach with a research location at the Sungguminasa Class 1B Religious Court. Data collection techniques in this research are interviews and documentation which are then processed through data reduction, data exposure, and conclusions. The results showed that the settlement of sharia economic disputes carried out by the Sungguminasa Class 1B Religious Court was in accordance with PERMA Number 5 of 2016. The PERMA states that sharia economic disputes must be handled by a panel of judges whose head of the panel or one of its members has sharia economic judge certification. In addition, the handling of sharia economic disputes at the Sungguminasa Religious Court is quite effective because the number of judges who have certified sharia economic judges is 2 judges, and 6 out of 7 decisions have been well received by each party to the dispute. This means that the decision has fulfilled the elements of an ideal decision, namely justice, legal certainty, and expediency. The implications of this research are: 1) All legal apparatus, especially judges of the Sungguminasa Religious Court, both those who have and those who have not been certified as sharia economic judges, should participate more in education and training on sharia economic disputes in order to be able to resolve sharia economic disputes better. 2) The Supreme Court as an institution that formulates PERMA Number 5 of 2016 should increase the budget allocation so that the implementation of sharia economic judge certification in the Religious Courts can be more effective. 3) The public in general is expected to increase trust in the Religious Court institution because the judges are ready to accept and face sharia economic disputes. Keywords: Religious Court, Sharia Economic Disputes, Sharia Economic Judge Certification